2010
DOI: 10.3844/ajavsp.2010.258.265
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Insulin on <i>in vitro</i> Development of Immature Bovine Oocytes

Abstract: Problem statement: Development of efficient culture system to support embryonic development would be valuable when quality of produced embryos was important. However, the rate of bovine embryo production in vitro was still lower than expected. Present study, including of three experiments, was carried out to investigate the effect of insulin on nuclear maturation and subsequent development of immature bovine oocytes and in vitro fertilized embryos. Approach: Grade one cumulus-oocyte-complexes harvested from sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It has been shown that insulin (0.1-10 μg/ml) enhanced the mitosis of bovine granulosa cells and accelerated progression of meiosis in oocytes enclosed with cumulus cells. Both granulosa cells and oocyte normally express insulin receptor (Dashtizad et al, 2010). In accordance with the present results regarding the significant reduction in percentage of degenerated oocytes by 10 μg/ml insulin, Wasielak and Bogacki (2007) found that the incidence of apoptotic DNA degeneration was reduced by addition of insulin, insulin like growth factor I (IGF I) and other growth factors to the maturation medium.…”
Section: Effect Of Insulin Levelsupporting
confidence: 91%
See 3 more Smart Citations
“…It has been shown that insulin (0.1-10 μg/ml) enhanced the mitosis of bovine granulosa cells and accelerated progression of meiosis in oocytes enclosed with cumulus cells. Both granulosa cells and oocyte normally express insulin receptor (Dashtizad et al, 2010). In accordance with the present results regarding the significant reduction in percentage of degenerated oocytes by 10 μg/ml insulin, Wasielak and Bogacki (2007) found that the incidence of apoptotic DNA degeneration was reduced by addition of insulin, insulin like growth factor I (IGF I) and other growth factors to the maturation medium.…”
Section: Effect Of Insulin Levelsupporting
confidence: 91%
“…The obtained data from the current study indicated an interaction effect between insulin and hormones (FSH, LH and E2) on embryonic stages atartig at M II. Similarly (Dashtizad et al, 2010) showed an interaction between insulin and FSH/or E2 on the bovine COCs. Also, Suzuki et al (2006) reported that stimulating effect of insulin on the proliferation of bovine granulosa cells is synergistic with gonadotrophins.…”
Section: Effect Of Interactionmentioning
confidence: 86%
See 2 more Smart Citations
“…After culturing oocytes in 0, 200, 800, and 2 000 pg/mL ghrelin during in vitro maturation of oocytes, Dovolou et al (73) found that ghrelin groups significantly suppressed blastocyst formation rates, whereas Dovolou et al (74) found no differences between the control, 200, and 2 000 pg/mL ghrelin groups, and fewer blastocysts were produced with 800 pg/mL than in the control group when the hormone was administered daily during the culture of zygotes. Dashtizad et al (75) reported that insulin at 10 μg/mL exerted beneficial effects on oocyte and embryo development up to the morula stage. E 2 and P 4 .…”
Section: Evidence On the Effect Of Hormonesmentioning
confidence: 99%